Non-communicable disease mortality in young people with a history of contact with the youth justice system in Queensland, Australia: a retrospective, population-based cohort study - Lucas Calais-Ferreira, PhD; Jesse T Young, PhD; Kate Francis, MBiostat; Melissa Willoughby, BA; Lindsay Pearce, MPH; Alan Clough, ProfPhD; Matthew J Spittal, ProfPhD; Alex Brown, ProfPhD; Rohan Borschmann, PhD; Susan M Sawyer, ProfPhD; George C Patton, ProfPhD; Stuart A Kinner, ProfPhD (Elsevier, 2023)
Summary: Background: Young people who have had contact with the criminal justice system are at increased risk of early death, especially from injuries. However, deaths due to non-communicable diseases (NCDs) in this population remain poorly described. We aimed to estimate mortality due to NCDs in people with a history of involvement with the youth justice system, compare NCD mortality rates in this population with those in the general population, and characterise demographic and justice-related factors associated with deaths caused by NCDs in people with a history of contact with the youth justice system. Methods: In this retrospective, population-based cohort study (the Youth Justice Mortality [YJ-Mort] study), we included all people aged 10-18 years (at baseline) charged with a criminal offence in Queensland, Australia, between June 30, 1993, and July 1, 2014. We probabilistically linked youth justice records with adult correctional records and national death records up to Jan 31, 2017. Indigenous status was ascertained from youth justice and adult correctional records, with individuals identified as Indigenous in either source classified as Indigenous in the final dataset. We estimated crude mortality rates and standardised mortality ratios (SMRs) for comparisons with data from the Australian general population. We identified risk factors for NCD deaths using competing-risks regression. Findings: Of 48 670 individuals aged 10-18 years (at baseline) charged with a criminal offence in Queensland, Australia, between June 30, 1993, and July 1, 2014, 11 897 (24·4%) individuals were female, 36 773 (75·6%) were male, and 13 250 (27·2%) were identified as identified as Indigenous. The median age at first contact with the youth justice system was 15 years (IQR 14-16), the median follow-up time was 13·4 years (8·4-18·4), and the median age at the end of the study was 28·6 years (23·6-33·6). Of 1431 deaths, 932 (65·1%) had a known and attributed cause, and 121 (13·0%) of these were caused by an NCD. The crude mortality rate from NCDs was 18·5 (95% CI 15·5-22·1) per 100 000 person-years among individuals with a history of involvement with the youth justice system, which was higher than among the age-matched and sex-matched Australian general population (SMR 1·67 [1·39-1·99]). Two or more admissions to adult custody (compared with none; adjusted sub-distribution hazard ratio 2·09 [1·36-3·22]), and up to 52 weeks in adult custody (compared with none; 1·98 [1·18-3·32]) was associated with NCD death. Interpretation: Young people with a history of contact with the justice system are at increased risk of death from NCDs compared with age-matched and sex-matched peers in the general Australian population. Reducing youth incarceration and providing young people's rights to access clinical, preventive, and restorative services should be a priority. Funding: National Health and Medical Research Council.